Effective lepton flavor violating Hij vertex from right-handed neutrinos within the mass insertion approximation - Arganda Carreras, Ernesto (2017)
In this work we present a new computation of the lepton flavor violating Higgs boson decays that are generated radiatively to one-loop from heavy right-handed neutrinos. We work within the context of the inverse seesaw model with three νR and three extra singlets X, but the results could be generalized to other low scale seesaw models. The novelty of our computation is that it uses a completely different method by means of the mass insertion approximation which works with the electroweak interaction states instead of the usual 9 physical neutrino mass eigenstates of the inverse seesaw model. This method also allows us to write the analytical results explicitly in terms of the most relevant model parameters, that are the neutrino Yukawa coupling matrix Yν and the right-handed mass matrix MR, which is very convenient for a phenomenological analysis. This Yν matrix, being generically nondiagonal in flavor space, is the only one responsible for the induced charged lepton flavor violating processes of our interest. We perform the calculation of the decay amplitude up to order O(Yν2+Yν4). We also study numerically the goodness of the mass insertion approximation results. In the last part we present the computation of the relevant one-loop effective vertex Hij for the lepton flavor violating Higgs decay which is derived from a large MR mass expansion of the form factors. We believe that our simple formula found for this effective vertex can be of interest for other researchers who wish to estimate the H→īj rates in a fast way in terms of their own preferred input values for the relevant model parameters Yν and MR.